Immune Checkpoint Inhibitor-Related Myositis Overlapping With Myocarditis: An Institutional Case Series and a Systematic Review of Literature - Nakagomi, Yuki; Tajiri, Kazuko; Shimada, Saori; Li, Siqi; Inoue, Keiko; Murakata, Yoshiko; Murata, Momoko; Sakai, Shunsuke; Sato, Kimi; Ieda, Masaki (Frontiers in Pharmacology, 2022)
Background: Immune checkpoint inhibitor (ICI)-related myositis with myocarditis is a rare but potentially fatal immune-related adverse event. However, its clinical features, response to immunosuppressive treatment, and prognosis remain poorly understood. Here, we describe the clinical course of patients with ICI-related myositis overlapping with myocarditis treated at our institution and a systematic review focusing on the response to immunosuppressive therapy. Methods: We identified patients who developed ICI-induced myositis with myocarditis and were treated at our hospital using a retrospective chart review of electronic medical records. For the systematic review, studies reporting ICI-induced myositis with myocarditis were identified using the Cochrane Library and PubMed databases. Results: Of the 625 patients treated with ICIs, four developed myositis with concurrent myocarditis. All the patients received immunosuppressive therapy. We assessed the activity of myocarditis and myositis based on temporal changes in troponin and creatine kinase (CK) levels. In all patients, peak troponin values appeared later than the peak CK values (median, 17 days). The median time from the start of ICI therapy to the peak of troponin and CK levels was 42.5 and 28 days, respectively. In all patients, CK levels decreased rapidly and steadily after the initiation of immunosuppressants. However, troponin levels were unstable and increased. In all patients, CK levels normalized within one month (range, 12–27 days), but troponin levels took several months to normalize (range, 84–161 days). Fourteen cases of ICI-related myositis with myocarditis were included in the systematic review. Of the 14 cases, 12 (86%) had their CK level decreased after the initial steroid treatment, but the troponin level increased and was higher than that before the start of treatment. In addition, the peak troponin values appeared later than the peak CK values (a median of 6.5 days). Eight (89%) of 9 long-term follow-up patients had troponin levels above the normal range even after CK normalization. Conclusion: In most cases of ICI-related myositis with myocarditis, troponin levels increased after the initial steroid treatment despite decreased CK levels, and exceeded pre-steroid levels. In addition, troponin remained elevated for several months after CK normalized.